2008
DOI: 10.1007/s00464-008-9828-9
|View full text |Cite
|
Sign up to set email alerts
|

Redefining contraindications to laparoscopic colorectal resection for high-risk patients

Abstract: In experienced hands, laparoscopic colorectal resection can be performed safely for "high-risk" surgical patients. The better than expected outcomes in this patient population reinforce the benefits of minimally invasive surgery for this patient group and argues against using parameters of increased age, morbid obesity, high ASA class, or preoperative radiation alone as contraindications to even complex laparoscopic colorectal procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(31 citation statements)
references
References 32 publications
(45 reference statements)
0
31
0
Order By: Relevance
“…18,19,28 However, analyses of our patients' postoperative hospital stays, time to recovery of full mobility, and analgesic requirements did not reveal significant differences between the 2 groups (e.g., mean hospital stays were 8.9 days for the mini-laparotomy group and 9.6 days for the laparoscopic group). This incongruence is likely due to patient selection; the majority of our patients required a VP shunt for bleeding-or tumor-related hydrocephalus.…”
Section: Time To Regain Full Mobility Analgesic Requirements and Lementioning
confidence: 61%
“…18,19,28 However, analyses of our patients' postoperative hospital stays, time to recovery of full mobility, and analgesic requirements did not reveal significant differences between the 2 groups (e.g., mean hospital stays were 8.9 days for the mini-laparotomy group and 9.6 days for the laparoscopic group). This incongruence is likely due to patient selection; the majority of our patients required a VP shunt for bleeding-or tumor-related hydrocephalus.…”
Section: Time To Regain Full Mobility Analgesic Requirements and Lementioning
confidence: 61%
“…Although most of the patients in this study had a diagnosis of cancer, the laparoscopic approach has been shown to provide similar improvements in short term outcomes in studies of patients were the sole indication was diverticulitis. [22][23][24] The safety of colorectal surgery in various high risk groups (high body mass index, ASA Grade Ն3, and age Ͼ80) was demonstrated by Marks et al 25 This could be an area of further research and review so the indications of laparoscopic colorectal resections can be expanded.…”
Section: Discussionmentioning
confidence: 97%
“…Average 30-d in-hospital mortality following colectomy has a wide variation in the literature ranging from 0% to 80% [4][5][6][7] secondary to the various diagnoses and often emergent presentations of patients. Different scoring systems have been created adjusting standards to accommodate for case-mix in order to calculate preoperative risk [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%